THE DIVIDED HOUSE OF CONSOLIDATIONS. - Sapienza, S. R. (The Accounting Review, 1960)
This paper emphasizes these points: 1. The minority interest is a stockholder equity interest and should be shown as such. 2. The variety of classifications presently used in showing the minority interest indicates that doubt exists as to its nature–liability, quasi-liability, or stockholder equity. 3. If the majority interest point of view is adopted, statements can be prepared from this standpoint and the minority can be brought along as a special stockholder equity interest. 4. Particularizing the minority share in retained earnings appears to be unnecessary since the total earnings is the same in the method described, and control over its disposition remains in the majority.